PENGEMBANGAN LEMBAR KERJA SISWA BAHASA INGGRIS BERBASIS KEARIFAN LOKAL JAWA DI SEKOLAH DASAR - Rosidah, Ulfa Khoirotul; Wati, Unik Ambar; Nurhayati (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2025)
Learning that integrates local wisdom can enrich students’ educational experiences by connecting them with their cultural heritage. However, research shows that integrating local wisdom, particularly Javanese culture, into the context of English language learning remains limited. This study aims to explore the validity and practicality of English student worksheets based on Javanese local wisdom as a supplementary learning resource in English instruction. The research employed a development method using the ADDIE (Analyze, Design, Develop, Implement, and Evaluate) model. Participants involved in the validation process included one media expert, one subject matter expert, two practitioners, and nineteen fourth-grade students from two elementary schools. Data were collected through observation, interviews, and questionnaires. Data analysis used qualitative and quantitative methods. The results of the study showed that the Javanese local wisdom-based English worksheets developed were “very feasible” based on the results of validation by media experts and subject matter experts, with a percentage of 88% each. The English worksheets based on Javanese local wisdom that were developed were “very practical” based on the percentage of teacher and student responses, with an average teacher response of 87.50% and an average student response of 83.79%. These results indicate that the Javanese local wisdom-based English worksheets are feasible and practical for use in English language learning. This study recommends the integration of local cultural elements into learning materials to foster student engagement and cultural appreciation while supporting student language development.